Near Surface Geophysical Imaging For Shallow Groundwater Flow Evaluation Using Electrical Resistivity And Self-Potential Methods - Olugbenga, Adeeko Tajudeen (2020)
The analysis of water flow in the earth subsurface is a vital issue to hydrogeology, environmental, geotechnical, and engineering studies. Despite this importance, less attention had been given to it which resulted in serious engineering and environmental hazard. This, therefore, necessitate the present study to mitigate the problem. The research aimed to study the near surface geophysical imaging for shallow groundwater flow in Archaeology gallery, Perpustakaan Hamzah Sendut 2, Sungai Batu, Lojing, and Kluang district Southern Peninsular Malaysia. To achieve this aim, 2-D resistivity, self-potential, and geotechnical methods were employed. The results reveal that anomaly -140 to 0 mV of self-potential is likely to be shallow groundwater flow recharge (infiltration) which established by 2-D resistivity inversion with low resistivity <100 Ωm at depth <5 m that accumulated in the region, which possibly indicate the presence of sandy silt, sandy clay and sand with the correlation of the geological setting of the study areas. From the result of particle size distribution curve, soil types and other parameters that can influence hydraulic conductivity (K) were determined. Furthermore, the soil layers were unconsolidated ranges from coarse sand, medium sand and other finer sediments which enhance water flow due to porosity and hydraulic conductivity factors. The hydraulic conductivity result (0.00009 to 0.001 m/s) shows that the soil is permeable, which relate to self-potential magnitude (0.3 to 3.7) of moderate size length. The samples used in this study were poorly graded soil condition because uniformity coefficient (CU) is greater than 4.